PENGARUH PROMOSI, KEMUDAHAN, DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN GOJEK ONLINE DI YOGYAKARTA - Khoiruddin, Muammar; Asteria, Beta (Jurnal Manajemen, 2023)
The purpose of this study is to determine the effectiveness of promotions, convenience, and service quality with regard to the needs of users of Gojek online in Yogyakarta. Utilizing the online Gojek application, this study was conducted. This sampling technique makes use of purposive sampling. Data analysis methodology use regressive linier berganda analysis with the SPSS version 25 application. The results of this study show that different promotions and service quality have a positive impact on customers of Gojek online in Yogyakarta. Then, for the variable kemudahan bearing a favorable sign, it did not indicate the number of Gojek online users in Yogyakarta. R2yaitu adjusted by Nilai dari is 0,503. With this in mind, it can be inferred that the concerns of Yogyakarta Gojek online users can be expressed through three independent variables: promotions, convenience, and service quality.